Dual-band intelligent window based on VO2 thermally induced phase change material, thin film and preparation method

By designing a photonic crystal film based on VO2 core-shell structure and installing a detachable high-reflection substrate, the shortcomings of traditional VO2 smart windows in solar radiation modulation and infrared radiation modulation performance are solved, and the intelligent thermal control effect with dual-band adjustable bands is achieved .

CN119493294AActive Publication Date: 2025-02-21UNIV OF ELECTRONICS SCI & TECH OF CHINA +2

Patent Information

Application Number
CN202411483867.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-21
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The problems of poor solar radiation modulation capabilities, single regulation bands, and the inconsistent infrared radiation modulation performance with intelligent thermal control requirements.

Method used

By designing a photonic crystal film based on VO2 core-shell structure, the solar radiation modulation capability of VO2 smart window is improved, and by installing a detachable high-reflection substrate on the photonic crystal film, the forward variable emissivity modulation performance of the infrared band is achieved.

Benefits of technology

The dual-band adjustable intelligent thermal control effect of VO2 smart window in the solar band (0.38~2.5μm) and the infrared band (2.5~14μm) is realized, improving energy saving effect and adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119493294A_ABST
    Figure CN119493294A_ABST
Patent Text Reader

Abstract

The invention provides a VO2 thermally induced phase change material-based dual-band intelligent window, a film and a preparation method thereof, and the dual-band intelligent window sequentially comprises X-coated VO2 core-shell particles, a visible light-to-infrared light transparent substrate and a visible light-to-infrared light reflection substrate from top to bottom; the X-coated VO2 core-shell particles are core-shell structure particle materials with visible light to infrared light transparent cores X inside and VO2-doped shell layers outside, and the X-coated VO2 core-shell particles are laid on a visible light to infrared light transparent substrate. The X-coated VO2 core-shell particles and the visible light-to-infrared light transparent substrate form a photonic crystal film, and the photonic crystal film is provided with a detachable visible light-to-infrared light reflection substrate. Compared with the prior art, the method has the advantages that (1) the sunlight modulation capability of a traditional VO2 intelligent window is improved; (2) the sunlight and infrared dual-band adjustable intelligent window is obtained; and (3) intelligent window devices with different phase change temperatures can be obtained so as to adapt to energy-saving regulation and control requirements of buildings in different regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dual-band smart window based on VO2 thermotropic phase change material, belonging to the technical field of engineering materials. Background Art

[0002] According to statistics, about 50% of building energy consumption is generated by indoor lighting, heating and cooling. Prioritizing the reduction of this part of energy loss will be the key to the green transformation of the construction industry. Window glass is the main channel for light and heat exchange between the indoor environment and the external environment. Therefore, it is regarded as an important breakthrough in solving the energy consumption problem. It is imperative to implement energy-saving transformation.

[0003] In this context, thermochromic windows have become cost-effective, intelligent and sensitive window solutions with their simple structure, passive light regulation capabilities without external energy, and high environmental responsiveness. The core indicators of its performance evaluation mainly include solar radiation transmittance modulation, which refers to the difference in solar transmittance under low and high temperature conditions within a specific wavelength range (0.38-2.5μm). This indicator is directly related to the energy-saving effect of windows. However, current research often ignores the emissivity modulation of windows in another key wavelength band-long-wave infrared (2.5-14μm), which is an area that needs to be further explored. Long-wave infrared radiation cooling technology, as an innovative strategy, can spontaneously release heat into the cold space by radiation, thereby achieving efficient cooling. In recent years, this technology has been widely used in a variety of scenarios, from radiation cooling devices below ambient temperature, energy-saving films, to smart fabrics, energy-saving roof coatings, etc., showing its broad application prospects.

[0004] However, it is worth noting that the traditional high-emissivity radiative cooling system has limitations. Its fixed high emissivity can only play a significant cooling role in warm weather. For areas that experience significant seasonal temperature changes, there is an urgent need for a radiative cooling system that can automatically adjust the emissivity according to seasonal changes to better adapt to the changing natural environment and further improve the energy efficiency and comfort of buildings. Summary of the invention

[0005] In order to solve the problems of poor solar radiation modulation capability and single regulation band of single VO2 film smart window, the present invention provides a photonic crystal film based on VO2 core-shell structure. The solar radiation modulation capability (0.38-2.5 μm) of the VO2 smart window is improved by structural design of the single VO2 film. In addition, by installing a detachable high-reflection substrate on the photonic crystal film, the forward variable emissivity modulation performance of the smart window in the infrared band (2.5-14 μm) can be achieved (the emissivity increases with increasing temperature), thereby obtaining a dual-band adjustable intelligent thermal control window device.

[0006] To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:

[0007] A dual-band smart window based on VO2 thermotropic phase change material, comprising, from top to bottom, X@VO2 core-shell particles, a visible light to infrared light transparent substrate 3, and a visible light to infrared light reflective substrate 4;

[0008] The X@VO2 core-shell particles are core-shell structured granular materials with a visible light to infrared light transparent core X1 inside and a VO2-doped shell layer 2 outside. The X@VO2 core-shell particles are used to achieve the transition between visible light to infrared light transmittance performance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate 3.

[0009] The X@VO2 core-shell particles and the visible light to infrared light transparent substrate 3 constitute a photonic crystal film, and the photonic crystal film is installed with a detachable visible light to infrared light reflecting substrate 4.

[0010] As a preferred embodiment, the VO2 smart window has the ability to modulate solar radiation from 0.38 to 2.5 μm. A removable visible light to infrared light reflecting substrate 4 is installed on the photonic crystal film, and the visible light to infrared light reflecting substrate 4 of the smart window is installed and removed according to different regions, climates and time periods to achieve regulation of the phase change temperature of VO2, thereby achieving the forward variable emissivity modulation performance of the smart window in the infrared band of 2.5 to 14 μm, and the emissivity increases with increasing temperature, thereby obtaining a dual-band adjustable intelligent thermal control window device in the solar band (0.38 to 2.5 μm) and the infrared band (2.5 to 14 μm).

[0011] As a preferred embodiment, the reflectivity of the visible light to infrared light reflective substrate 4 is greater than 90%.

[0012] And / or the visible light to infrared light reflecting substrate 4 is a copper sheet, an aluminum sheet or a flexible tin foil,

[0013] As a preferred embodiment, the visible light to infrared light transparent core X1 is a spherical particle of calcium fluoride, zinc sulfide, zinc selenide or barium fluoride with a visible light to infrared transmittance greater than 90%, and the particle size is 300nm-700nm.

[0014] As a preferred embodiment, the thickness of the doped VO2 shell layer 2 is 20nm-60nm;

[0015] And / or the doped VO2 shell layer 2 is doped with tungsten, molybdenum, and boron elements to reduce its phase transition temperature.

[0016] As a preferred embodiment, the visible light to infrared light transparent substrate 3 is calcium fluoride, barium fluoride, zinc sulfide or zinc selenide;

[0017] And / or the transmittance of the visible light to infrared light transparent substrate 3 is greater than 90%.

[0018] As a preferred method, X@VO2 core-shell particles are laid flat on a visible to infrared light transparent substrate 3 in a monolayer by self-assembly to obtain a photonic crystal film;

[0019] And / or the photonic crystal film is connected to the visible light to infrared light reflecting substrate 4 via a fixing bracket, and is installed and disassembled according to different weather or climate.

[0020] The second object of the present invention is to provide a photonic crystal film based on VO2 thermotropic phase change material, which comprises, from top to bottom, X@VO2 core-shell particles, a visible light to infrared light transparent substrate 3;

[0021] The X@VO2 core-shell particles are core-shell structured granular materials with a visible light to infrared light transparent core X1 inside and a VO2-doped shell layer 2 outside. The X@VO2 core-shell particles are used to achieve the transition between visible light to infrared light transmittance performance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate 3.

[0022] The third object of the present invention is to provide a method for preparing the X@VO2 core-shell particle photonic crystal film, comprising the following steps:

[0023] Step 1: Prepare microspheres of core material X with a particle size of 300nm-700nm by a hydrothermal method, and set aside;

[0024] Step 2: Preparation of X@VO by solvent hydrothermal method x Core-shell particles:

[0025] A certain amount of vanadium source and reducing agent are dissolved in an aqueous solution to obtain a VO2 precursor solution, wherein the molar ratio of the vanadium source to the reducing agent is 1 to 3; the core material X microspheres prepared in step 1 are uniformly dispersed in a solvent, a dopant, a precipitant and a surfactant are added, and the mixture is uniformly mixed to obtain an X microsphere solution, wherein the mass ratio of the dopant to the vanadium source is 1% to 7%; the mass ratio of the precipitant to the vanadium source is 5% to 10%, and the mass ratio of the surfactant to the vanadium source is 5% to 20%. The VO2 precursor solution prepared in step 1 is added to the X microsphere solution at a molar ratio of X:VO2 of 3 to 5, and X@VO2 is prepared by a solvothermal method. x powder;

[0026] Step 3: X@VO prepared in step 2 x The powder is calcined in a certain atmosphere to promote VO x The shell layer transforms to M phase, and the doped M phase X@VO2(M) core-shell material is obtained;

[0027] Step 4, preparing nano-scale X@VO2 photonic crystals by vertical deposition self-assembly method;

[0028] The spherical M phase X@VO2(M) was dispersed in deionized water and ultrasonically dispersed for a period of time to prepare a microsphere suspension. Then, the cleaned hydrophilic glass substrate was vertically immersed in the microsphere suspension and dried at a constant temperature.

[0029] As the mixed solvent evaporates, the spherical X@VO2 self-assembles into a single-layer photonic crystal film on the substrate surface.

[0030] As a preferred embodiment, in the method for preparing the X@VO2 core-shell particle photonic crystal film, the vanadium source in step 2 is vanadium pentoxide, vanadyl sulfate or ammonium metavanadate, and the reducing agent is oxalic acid or citric acid;

[0031] And / or the solvent is n-propanol, ethylene glycol or benzyl alcohol; the doping agent is ammonium molybdate, sodium tungstate or boric acid; the precipitating agent is urea; the surfactant is dopamine;

[0032] And / or the solvent thermal reaction condition is 210° C. for 24 hours.

[0033] And / or the atmosphere calcination in step 3 is carried out at an oxygen partial pressure R O2 =V O2 / (V O2 +V N2 )=5% and keep warm at 500℃ for 30min.

[0034] Beneficial Effects

[0035] (1) Traditional VO2 thin film energy-saving windows have certain limitations in performance. They cannot simultaneously achieve the characteristics of high transmittance at low temperatures and low transmittance at high temperatures (poor solar light modulation performance), and thus cannot achieve ideal energy-saving effects as the climate changes. The present invention proposes an energy-saving window device based on a VO2 core-shell structure. By structurally designing the VO2 thin film, the VO2 core-shell structure photonic crystal obtained can significantly improve the solar radiation modulation performance (0.38-2.5 μm) of the energy-saving window.

[0036] (2) The energy-saving effect of VO2 smart window is not only related to the sunlight modulation performance, but also to the infrared radiation (emission) modulation performance. The infrared modulation performance of a single VO2 is opposite to the requirements of intelligent thermal control (the emissivity decreases with increasing temperature). The present invention designs an energy-saving window device with a VO2 core-shell structure. By installing a detachable high-reflection substrate on the VO2 photonic crystal film, the smart window can achieve the inversion of the variable emissivity performance in the infrared band (2.5-14μm), that is, the emissivity increases with increasing temperature, which meets the requirements of intelligent thermal control.

[0037] (3) Vanadium dioxide (VO2) undergoes a reversible phase transition from a low-temperature insulating state to a high-temperature metallic state at 68°C, resulting in a change in its optical properties, thereby enabling its use in smart windows. However, the high phase transition temperature limits its practical application. The present invention dopes VO2 with elements such as tungsten, molybdenum, and boron to reduce the phase transition temperature of the smart window device, and by controlling the doping amounts of different elements, smart window devices with different phase transition temperatures can be obtained to meet the energy-saving regulation needs of buildings in different regions.

[0038] In summary, compared with the prior art, the present invention has the following significant advantages: (1) It improves the solar modulation capability of the traditional VO2 smart window; (2) It obtains a smart window that is adjustable in both sunlight and infrared bands; (3) It can obtain smart window devices with different phase change temperatures to meet the energy-saving and control needs of buildings in different regions. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the structure and principle of the dual-band smart window of the present invention.

[0040] Figure 2 The modulation performance of VO2 photonic crystal in the solar light band (without installation of visible to infrared light reflective substrate).

[0041] Figure 3 The modulation performance of VO2 smart window in the infrared light band (installed with visible light to infrared light reflecting substrate).

[0042] 1-visible light to infrared light transparent core X, 2-doped VO2 shell, 3-visible light to infrared light transparent substrate, 4-visible light to infrared light reflecting substrate. DETAILED DESCRIPTION

[0043] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0044] like Figure 1As shown, the dual-band smart window based on VO2 thermotropic phase change material of the present invention first obtains doped VO2 core-shell particles by water / solvent thermal-high temperature calcination method; then, a single layer of X@VO2 core-shell particles is laid flat on a visible light to infrared light transparent substrate 3 carrier plate by self-assembly method to obtain a VO2 photonic crystal smart window with high modulation performance for sunlight; finally, a visible light to infrared light reflective substrate 4 is fixed to the bottom of the carrier plate by a bracket to obtain a smart thermal control window with high radiation modulation performance in the infrared band. During use, the high reflective substrate of the smart window can be installed and disassembled according to different regions, climates and time periods, and the phase change temperature of VO2 can be adjusted to meet the energy-saving regulation requirements of different buildings.

[0045] The performance of the smart window proposed in this invention is analyzed through simulation. Figure 2 The modulation performance of VO2 photonic crystal in the sunlight band (without the visible to infrared light reflective substrate), where the core material is barium fluoride, with a particle size of 500nm and a shell thickness of 35nm, and the glass slide is calcium fluoride with a thickness of 2000nm. As can be seen from the figure, the transmittance of the smart window in the sunlight band decreases as the temperature rises, and the modulation performance at the 2.5μm band is greater than 0.75 (transmittance difference), which can be improved by about 50% compared with the traditional VO2 film (modulation performance is about 0.5).

[0046] Figure 3 The modulation performance of the VO2 smart window in the infrared band (installed with a visible light to infrared light reflective substrate), where the visible light to infrared light reflective substrate is tin foil with a thickness of 2mm. As can be seen from the figure, the infrared emissivity of the smart window increases with the increase of temperature, and the emissivity change value at high and low temperatures in the 2-14μm band is greater than 0.55. At low temperatures, the window can have lower radiation characteristics to achieve heat preservation. As the temperature rises, the emissivity increases, and the corresponding window can dissipate heat through radiation heat dissipation, thereby playing a role in cooling and ultimately achieving the purpose of intelligent temperature control.

[0047] Example 1 A dual-band smart window based on VO2 thermotropic phase change material

[0048] like Figure 1 As shown, the embodiment provides a dual-band smart window based on VO2 thermotropic phase change material, which comprises, from top to bottom, X@VO2 core-shell particles, a visible light to infrared light transparent substrate 3 and a visible light to infrared light reflective substrate 4;

[0049] The X@VO2 core-shell particles are core-shell structured granular materials with a visible light to infrared light transparent core X1 inside and a VO2-doped shell layer 2 outside. The X@VO2 core-shell particles are used to achieve the transition between visible light to infrared light transmittance performance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate 3.

[0050] The X@VO2 core-shell particles and the visible light to infrared light transparent substrate 3 constitute a photonic crystal film, and the photonic crystal film is installed with a detachable visible light to infrared light reflecting substrate 4.

[0051] The VO2 smart window has the ability to modulate solar radiation from 0.38 to 2.5 μm. A detachable visible light to infrared light reflecting substrate 4 is installed on the photonic crystal film. The visible light to infrared light reflecting substrate 4 of the smart window is installed and removed according to different regions, climates and time periods to achieve regulation of the phase change temperature of VO2, thereby achieving the forward variable emissivity modulation performance of the smart window in the infrared band of 2.5 to 14 μm. The emissivity increases with increasing temperature, thereby obtaining a dual-band adjustable intelligent thermal control window device in the solar band and the infrared band.

[0052] Preferably, the reflectivity of the visible light to infrared light reflective substrate 4 is greater than 90%.

[0053] And / or the visible light to infrared light reflecting substrate 4 is a copper sheet, an aluminum sheet or a flexible tin foil,

[0054] Preferably, the visible light to infrared light transparent core X1 is a spherical particle of calcium fluoride, zinc sulfide, zinc selenide or barium fluoride with a visible light to infrared transmittance greater than 90%, and the particle size is 300nm-700nm.

[0055] Preferably, the thickness of the doped VO2 shell layer 2 is 20nm-60nm;

[0056] And / or the doped VO2 shell layer 2 is doped with tungsten, molybdenum, and boron elements to reduce its phase transition temperature.

[0057] Preferably, the visible light to infrared light transparent substrate 3 is calcium fluoride, barium fluoride, zinc sulfide or zinc selenide;

[0058] And / or the transmittance of the visible light to infrared light transparent substrate 3 is greater than 90%.

[0059] Example 2 A dual-band smart window based on VO2 thermotropic phase change material

[0060] A dual-band smart window based on VO2 thermotropic phase change material, X@VO2 core-shell particles are laid flat on a visible to infrared transparent substrate 3 in a single layer by self-assembly to obtain a photonic crystal film;

[0061] And / or the photonic crystal film is connected to the visible light to infrared light reflecting substrate 4 via a fixing bracket, and is installed and disassembled according to different weather or climate.

[0062] Example 3 A photonic crystal film based on VO2 thermoinduced phase change material

[0063] A photonic crystal film based on VO2 thermoinduced phase change material, which comprises, from top to bottom, X@VO2 core-shell particles and a visible light to infrared light transparent substrate 3;

[0064] The X@VO2 core-shell particles are core-shell structured granular materials with a visible light to infrared light transparent core X1 inside and a VO2-doped shell layer 2 outside. The X@VO2 core-shell particles are used to achieve the transition between visible light to infrared light transmittance performance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate 3.

[0065] Example 4 A method for preparing a X@VO2 core-shell particle photonic crystal film,

[0066] A method for preparing a X@VO2 core-shell particle photonic crystal film comprises the following steps:

[0067] Step 1: Prepare microspheres of core material X with a particle size of 300nm-700nm by a hydrothermal method, and set aside;

[0068] Step 2: Preparation of X@VO by solvent hydrothermal method x Core-shell particles:

[0069] A certain amount of vanadium source and reducing agent are dissolved in an aqueous solution to obtain a VO2 precursor solution, wherein the molar ratio of the vanadium source to the reducing agent is 1 to 3; the core material X microspheres prepared in step 1 are uniformly dispersed in a solvent, a dopant, a precipitant and a surfactant are added, and the mixture is uniformly mixed to obtain an X microsphere solution, wherein the mass ratio of the dopant to the vanadium source is 1% to 7%; the mass ratio of the precipitant to the vanadium source is 5% to 10%, and the mass ratio of the surfactant to the vanadium source is 5% to 20%. The VO2 precursor solution prepared in step 1 is added to the X microsphere solution at a molar ratio of X:VO2 of 3 to 5, and X@VO2 is prepared by a solvothermal method. x powder;

[0070] Step 3: X@VO prepared in step 2 x The powder is calcined in a certain atmosphere to promote VO x The shell layer transforms to M phase, and the doped M phase X@VO2(M) core-shell material is obtained;

[0071] Step 4, preparing nano-scale X@VO2 photonic crystals by vertical deposition self-assembly method;

[0072] The spherical M phase X@VO2(M) was dispersed in deionized water and ultrasonically dispersed for a period of time to prepare a microsphere suspension. Then, the cleaned hydrophilic glass substrate was vertically immersed in the microsphere suspension and dried at a constant temperature.

[0073] As the mixed solvent evaporates, the spherical X@VO2 self-assembles into a single-layer photonic crystal film on the substrate surface.

[0074] In some embodiments, in the method for preparing a photonic crystal film, the vanadium source in step 2 is vanadium pentoxide, vanadyl sulfate or ammonium metavanadate, and the reducing agent is oxalic acid or citric acid;

[0075] And / or the solvent is n-propanol, ethylene glycol or benzyl alcohol; the doping agent is ammonium molybdate, sodium tungstate or boric acid; the precipitating agent is urea; the surfactant is dopamine;

[0076] And / or the solvent thermal reaction condition is 210° C. for 24 hours.

[0077] And / or the atmosphere calcination in step 3 is carried out at an oxygen partial pressure R O2 =V O2 / (V O2 +V N2 )=5% and keep warm at 500℃ for 30min.

[0078] Example 5

[0079] Preparation of doped BaF2@VO2 core-shell particles:

[0080] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 6.0 with alkaline solutions such as NaOH and ammonium water. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0081] Step 2: Use vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and use the solvothermal method to coat a layer of Mo-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then add a certain amount of ammonium molybdate and urea, and continue stirring for 30min to obtain the doped VO2 precursor solution A. Weigh 0.2g of BaF2 and add it to 35ml isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 500°C for 30 minutes, BaF2@V 1-x Mo x O2(M) target product.

[0082] Preparation of VO2 core-shell structure photonic crystals:

[0083] Soak the CaF2 glass slide in 30% H2O2 for 24 hours, then wash the glass slide with deionized water and anhydrous ethanol respectively. After the glass slide is dry, place it in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.023g of the prepared BaF2@V 1-x Mo x O2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xMoxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0084] Embodiment 6:

[0085] Preparation of doped BaF2@VO2 core-shell particles:

[0086] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 6.0 with alkaline solutions such as NaOH and ammonium water. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0087] Step 2: Use vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and use the solvothermal method to coat a layer of Mo-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then add a certain amount of ammonium molybdate and urea, and continue stirring for 30min to obtain the doped VO2 precursor solution A. Weigh 0.2g of BaF2 and add it to 35ml isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 500°C for 30 minutes, BaF2@V 1-x Mo x O2(M) target product.

[0088] Preparation of VO2 core-shell structure photonic crystals:

[0089] Soak the CaF2 glass slide in 30% H2O2 for 24 hours, then wash the glass slide with deionized water and anhydrous ethanol respectively. After the glass slide is dry, place it in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.023g of the prepared BaF2@V 1-x Mo xO2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xMoxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0090] A visible light to infrared light reflecting substrate 4 copper sheet is installed at the bottom of the obtained VO2 core-shell structure photonic crystal.

[0091] Embodiment 7:

[0092] Preparation of doped BaF2@VO2 core-shell particles:

[0093] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 6.0 with alkaline solutions such as NaOH and ammonium water. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0094] Step 2: Use vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and use the solvothermal method to coat a layer of Mo-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then add a certain amount of ammonium molybdate and urea, and continue stirring for 30min to obtain the doped VO2 precursor solution A. Weigh 0.2g of BaF2 and add it to 35ml isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 500°C for 30 minutes, BaF2@V 1-x Mo x O2(M) target product.

[0095] Preparation of VO2 core-shell structure photonic crystals:

[0096] Soak the CaF2 glass slide in 30% H2O2 for 24 hours, then wash the glass slide with deionized water and anhydrous ethanol respectively. After the glass slide is dry, place it in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.04g of the prepared BaF2@V 1-x Mo x O2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xMoxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0097] Embodiment 8:

[0098] Preparation of doped BaF2@VO2 core-shell particles:

[0099] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 6.0 with alkaline solutions such as NaOH and ammonium water. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0100] Step 2, using vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and using the solvothermal method to coat a layer of W-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml of deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then a certain amount of ammonium tungstate and urea were added, and stirring continued for 30min to obtain the doped VO2 precursor solution A. Weigh 0.2g of BaF2 and add it to 35ml of isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 500°C for 30 minutes, BaF2@V 1-x W x O2(M) target product.

[0101] Preparation of VO2 core-shell structure photonic crystals:

[0102] Soak the CaF2 glass slide in 30% H2O2 for 24 hours, then wash the glass slide with deionized water and anhydrous ethanol respectively. After the glass slide is dry, place it in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.023g of the prepared BaF2@V 1-x Mo xO2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xWxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0103] A visible to infrared light reflecting base aluminum sheet is installed at the bottom of the obtained VO2 core-shell structure photonic crystal.

[0104] Embodiment 9:

[0105] Preparation of doped BaF2@VO2 core-shell particles:

[0106] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 6.0 with ammonium water. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0107] Step 2: Use vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and use the solvothermal method to coat a layer of Mo-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then add a certain amount of ammonium molybdate and urea, and continue stirring for 30min to obtain doped VO2 precursor solution A. Weigh 0.4g of BaF2 and add it to 35ml isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 500°C for 30 minutes, BaF2@V 1-x Mo x O2(M) target product.

[0108] Preparation of VO2 core-shell structure photonic crystals:

[0109] Soak the CaF2 glass slide in 30% H2O2 for 24 hours, then wash the glass slide with deionized water and anhydrous ethanol respectively. After the glass slide is dry, place it in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.023g of the prepared BaF2@V 1-x Mo x O2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xMoxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0110] Embodiment 10:

[0111] Preparation of doped BaF2@VO2 core-shell particles:

[0112] Step 1, dissolve 2mmol BaCl2 and 4mmol ethylenediaminetetraacetic acid in 50ml deionized water and stir until completely dissolved. Then slowly add 20ml NaBF4 (4mmol) solution to the above solution. Adjust the pH value of the final solution to 4.0 with NaOH. After stirring for about 30 minutes, transfer the resulting suspension to a polytetrafluoroethylene liner (100mL), place it in a stainless steel autoclave, seal it, and react at 190°C for 6 hours. As the autoclave naturally cools to room temperature, the precipitate is separated by centrifugation and then washed with deionized water and ethanol in turn. Finally, the precipitate is dried in air at 70°C for 24h to obtain the final BaF2 microspheres.

[0113] Step 2: Use vanadium pentoxide (V2O5) as the vanadium source and oxalic acid (H2C2O4) as the reducing agent to prepare the precursor solution, and use the solvothermal method to coat a layer of Mo-doped VO2 on the BaF2 core particles. First, vanadium pentoxide and oxalic acid were mixed in 10ml deionized water at a molar ratio of 1:3. After stirring in a constant temperature water bath at 50°C for 30min, the solution changed from yellow to blue. Then add a certain amount of ammonium molybdate and urea, and continue stirring for 30min to obtain the doped VO2 precursor solution A. Weigh 0.2g of BaF2 and add it to 35ml isopropanol solution, ultrasonicate until uniformly dispersed, then add a certain amount of morphology agent dopamine, and stir evenly for 30min to obtain solution B. Then take 2ml of A solution and slowly add it to B solution, continue stirring for 30min to obtain a uniformly mixed C solution. Finally, transfer C solution to a 50ml polytetrafluoroethylene reactor and react at 210°C for 14h. After the reaction is completed, the inner substrate bottom powder is repeatedly washed with deionized water and dried at 70°C for 5 hours to obtain Mo-doped BaF2@VO2(D) double-layer core-shell particles. Finally, the dried BaF2@VO2(D) powder is calcined at 550°C for 1.5 hours in a nitrogen atmosphere. At this time, the shell VO2 will be reduced to V2O3. A certain proportion of oxygen and nitrogen are then introduced, and the pressure in the vacuum tube furnace is kept constant. After being kept at 600°C for 30 minutes, BaF2@V 1-x Mo x O2(M) target product.

[0114] Preparation of VO2 core-shell structure photonic crystals:

[0115] The ZnS glass slide was soaked in 30% H2O2 for 24 hours and then washed with deionized water and anhydrous ethanol respectively. After the glass slide was dried, it was placed in a plasma cleaner for hydrophilic treatment for 50 minutes. Weigh 0.023g of the prepared BaF2@V 1-x Mo xO2(M) powder and disperse it in 10mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes using a cell ultrasonic crusher to obtain a BaF2@V1-xMoxO2(M) dispersion system with a mass fraction of 0.3%. Finally, two hydrophilic-treated glass slides were fixed and assembled, vertically inserted into the above dispersion system, and dried at a constant temperature in a 45°C oven. After the solution was completely evaporated, a film-like photonic crystal was obtained on the glass slide.

[0116] A visible to infrared light reflecting substrate copper sheet is installed at the bottom of the obtained VO2 core-shell structure photonic crystal.

[0117] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A dual-band smart window based on VO2 thermotropic phase change material, characterized by: From top to bottom, they are X@VO2 core-shell particles, visible light to infrared light transparent substrate (3), and visible light to infrared light reflecting substrate (4); The X@VO2 core-shell particles are core-shell structured particle materials with a visible light to infrared light transparent core X (1) inside and a VO2 doped shell layer (2) outside. The X@VO2 core-shell particles are used to achieve the transition between visible light and infrared light transmittance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate (3). X@VO2 core-shell particles and a visible light to infrared light transparent substrate (3) constitute a photonic crystal film, and a detachable visible light to infrared light reflective substrate (4) is installed on the photonic crystal film.

2. According to claim 1, a dual-band smart window based on VO2 thermotropic phase change material, characterized in that: The VO2 smart window has a solar radiation modulation capability of 0.38 to 2.5 μm. A detachable visible light to infrared light reflecting substrate (4) is installed on a photonic crystal film. The visible light to infrared light reflecting substrate (4) of the smart window is installed and removed according to different regions, climates and time periods, so as to achieve regulation of the phase change temperature of VO2, thereby achieving the forward variable emissivity modulation performance of the smart window in the 2.5 to 14 μm infrared band. The emissivity increases with increasing temperature, thereby obtaining a dual-band adjustable smart thermal control window device in the solar band and the infrared band.

3. According to claim 1, a dual-band smart window based on VO2 thermotropic phase change material, characterized in that: The reflectivity of the visible to infrared light reflective substrate (4) is greater than 90%, And / or the visible light to infrared light reflecting substrate (4) is a copper sheet, an aluminum sheet or a flexible tin foil.

4. According to claim 1, a dual-band smart window based on VO2 thermotropic phase change material, characterized in that: The visible light to infrared light transparent core X(1) is a spherical particle of calcium fluoride, zinc sulfide, zinc selenide or barium fluoride with a visible light to infrared transmittance greater than 90%, and the particle size is 300nm-700nm.

5. According to claim 1, a dual-band smart window based on VO2 thermotropic phase change material, characterized in that: The thickness of the doped VO2 shell layer (2) is 20nm-60nm; And / or the doped VO2 shell layer (2) is doped with tungsten, molybdenum or boron elements to reduce its phase transition temperature.

6. According to claim 1, a dual-band smart window based on VO2 thermotropic phase change material, characterized in that: The visible light to infrared light transparent substrate (3) is calcium fluoride, barium fluoride, zinc sulfide or zinc selenide; And / or the transmittance of the visible light to infrared light transparent substrate (3) is greater than 90%.

7. The dual-band smart window based on VO2 thermotropic phase change material according to claim 1, characterized in that: X@VO2 core-shell particles are laid flat in a single layer on a visible to infrared light transparent substrate (3) by self-assembly to obtain a photonic crystal film; And / or the photonic crystal film is connected to the visible light to infrared light reflecting substrate (4) via a fixed bracket, and is installed and disassembled according to different weather or climate.

8. A photonic crystal film based on VO2 thermotropic phase change material, characterized in that: From top to bottom, they are X@VO2 core-shell particles and visible to infrared light transparent substrate (3); The X@VO2 core-shell particles are core-shell structured particle materials with a visible light to infrared light transparent core X (1) inside and a VO2 doped shell layer (2) outside. The X@VO2 core-shell particles are used to achieve the transition between visible light and infrared light transmittance. The X@VO2 core-shell particles are spread on a visible light to infrared light transparent substrate (3).

9. A method for preparing a photonic crystal film based on VO2 thermotropic phase change material according to claim 8, characterized in that: The following steps are involved: Step 1: Prepare microspheres of core material X with a particle size of 300nm-700nm by a hydrothermal method, and set aside; Step 2: Preparation of X@VO by solvent hydrothermal method x Core-shell particles: A certain amount of vanadium source and reducing agent are dissolved in an aqueous solution to obtain a VO2 precursor solution, wherein the molar ratio of the vanadium source to the reducing agent is 1 to 3; the core material X microspheres prepared in step 1 are uniformly dispersed in a solvent, a dopant, a precipitant and a surfactant are added, and the mixture is uniformly mixed to obtain an X microsphere solution, wherein the mass ratio of the dopant to the vanadium source is 1% to 7%; the mass ratio of the precipitant to the vanadium source is 5% to 10%, and the mass ratio of the surfactant to the vanadium source is 5% to 20%. The VO2 precursor solution prepared in step 1 is added to the X microsphere solution at a molar ratio of X:VO2 of 3 to 5, and X@VO2 is prepared by a solvothermal method. x powder; Step 3: X@VO prepared in step 2 x The powder is calcined in a certain atmosphere to promote VO x The shell layer transforms to M phase, and the doped M phase X@VO2(M) core-shell material is obtained; Step 4, preparing nano-scale X@VO2 photonic crystals by vertical deposition self-assembly method; The spherical M phase X@VO2(M) was dispersed in deionized water and ultrasonically dispersed for a period of time to prepare a microsphere suspension. Then, the cleaned hydrophilic glass substrate was vertically immersed in the microsphere suspension and dried at a constant temperature. As the mixed solvent evaporates, the spherical X@VO2 self-assembles into a single-layer photonic crystal film on the substrate surface.

10. The method for preparing a photonic crystal film based on VO2 thermotropic phase change material according to claim 9, characterized in that: The vanadium source in step 2 is vanadium pentoxide, vanadyl sulfate or ammonium metavanadate, and the reducing agent is oxalic acid or citric acid; And / or the solvent is n-propanol, ethylene glycol or benzyl alcohol; the doping agent is ammonium molybdate, sodium tungstate or boric acid; the precipitating agent is urea; the surfactant is dopamine; And / or the solvent thermal reaction condition is 210° C. for 24 hours; And / or the atmosphere calcination in step 3 is carried out at an oxygen partial pressure R O2 =V O2 / (V O2 +V N2 )=5% and keep warm at 500℃ for 30min.

Citation Information

Patent Citations

  • Method for preparing VO2 core-shell structure

    CN103205249A

  • Core-shell nanoparticle, film, glazing unit, double glazing unit and method of making a glazing unit

    CN103502554A

  • Flexible film with adjustable infrared emissivity and preparation method thereof

    CN111077603A

  • Thermally-induced variable-emissivity intelligent temperature control coating based on VO2 core-shell structure

    CN113185863A

  • Radiation refrigeration film based on phase change material

    CN214469444U

Cited By

  • Preparation method for improving driving performance of stimuli-responsive polymer film

    CN121021886A

  • A preparation method for improving the driving performance of a stimuli-responsive polymer film

    CN121021886B